2021
DOI: 10.7150/thno.58799
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in critical nodes of embryo engineering technology

Abstract: The normal development and maturation of oocytes and sperm, the formation of fertilized ova, the implantation of early embryos, and the growth and development of foetuses are the biological basis of mammalian reproduction. Therefore, research on oocytes has always occupied a very important position in the life sciences and reproductive medicine fields. Various embryo engineering technologies for oocytes, early embryo formation and subsequent developmental stages and different target sites, such as gene editing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 224 publications
(227 reference statements)
0
4
0
2
Order By: Relevance
“…In addition, we can confirm that it can improve the developmental ability of embryos during early development [29]. The in vitro development of embryos is inefficient compared to embryos derived in vivo [34]; embryos cultured in vitro exhibit increased ROS levels, especially SCNT embryos during the process of micromanipulation in vitro [35]. SCNT technology in embryos can also cause damage to mitochondrial membrane potential, DNA, and gene and protein expression [35,36].…”
Section: Discussionmentioning
confidence: 82%
“…In addition, we can confirm that it can improve the developmental ability of embryos during early development [29]. The in vitro development of embryos is inefficient compared to embryos derived in vivo [34]; embryos cultured in vitro exhibit increased ROS levels, especially SCNT embryos during the process of micromanipulation in vitro [35]. SCNT technology in embryos can also cause damage to mitochondrial membrane potential, DNA, and gene and protein expression [35,36].…”
Section: Discussionmentioning
confidence: 82%
“…The increased metabolism leads to the formation of new cells in growing embryos. It could be suggested that the presence of one of the main factors in FBS is phosphate, and the concentration is higher as inorganic phosphorus can stimulate the development of eight-cell embryos in a rat model [ 26 ]. Moreover, it was also found that adding FBS on day 4 also improved the hatching and hatched BL formation compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Trong thao tác ICSI, lực tác động lên zona pellucida (lực xuyên ZP) cũng là một yếu tố vô cùng quan trọng, tác dụng lực quá lớn có thể gây ra những tổn thương không thể phục hồi cho tế bào noãn [13]. Để đánh giá cũng như hạn chế những tổn thương đến noãn trong quá trình ICSI, nhiều công nghệ mới đã được áp dụng với hy vọng có thể đo đạc và kiểm soát lực xuyên ZP.…”
Section: Kiểm Soát Lực Xuyên Màngunclassified
“…Bên cạnh đo trực tiếp, các phương pháp đo gián tiếp cũng đã được đề xuất, bao gồm phương pháp đo dựa trên thị giác máy tính, phương pháp tính toán giải lực thông qua các hàm lực khác nhau hoặc ước tính gián tiếp lực xuyên màng thông qua đầu vào của bộ truyền động. Trong các báo cáo, phương pháp đo lực gián tiếp thường cho độ chính xác kém hơn hẳn so với đo trực tiếp [13]. Mục đích cuối cùng của việc tìm kiếm các phương pháp đo lường chính xác lực xuyên màng của các nhà nghiên cứu là mong muốn xây dựng hệ thống ICSI mà người ICSI hoàn toàn có thể kiểm soát lực này trong giới hạn cho phép.…”
Section: Kiểm Soát Lực Xuyên Màngunclassified